Disentangling the Potato Tuber Moth-Induced Early-Defense Response by Simulated Herbivory in Potato Plants - Mao, Zhiyao; Ge, Yang; Zhang, Yadong; Zhong, Jian; Munawar, Asim; Zhu, Zengrong; Zhou, Wenwu (Frontiers in Plant Science, 2022)
Plants rely on the perception of a multitude of herbivory-associated cues (HACs) to activate their defense response to insect herbivores. These stimuli are mainly derived from three functional components: mechanical damage, insect-associated microbe, and insect’s chemical cues. While simulated herbivory integrating these stimuli is widely exploited for complementing actual herbivory in clarifying the details of plant-herbivore interaction, breaking down these stimuli and identifying the mechanisms of plant responses associated with them have been less explored. In this study, the components of potato tuber moth (Phthorimaea operculella, PTM) herbivory were reorganized in a cumulative way and their impacts on the early defense responses of potato leaf were characterized. We found that simulated and actual herbivory of PTM triggered similar patterns of phytohormonal and transcriptomic responses in potato leaf. Moreover, the microbe in the PTM herbivory stimuli is associated with the regulation of the phytohormones jasmonic acid (JA) and abscisic acid (ABA), since reducing the microbe in HAC could reduce JA while increase ABA. In addition, seven robust gene modules were identified to illustrate how potato plants respond to different PTM herbivory stimuli when herbivory components increased. Significantly, we found that mechanical damage mainly activated JA-mediated signaling; PTM-derived HACs contributed much more to potato early defense response and induced signaling molecules such as multiple protein kinases; orally secreted bacteria stimuli could antagonize PTM-derived HACs and modulate plant defense including repressing phenylpropanoid biosynthesis. Our study broadened the understanding of how potato plants integrate the responses to a multitude of stimuli upon PTM herbivory and evidenced that insect-associated microbes greatly modulated the plants response to insect herbivory.